Physical Characteristics, Inorganic Constituents and Trace Metals Determination in the Street-Vended Samples of Heroin (Biological Sciences - PJSIR, 2006)
Samples of heroin collected from different parts of NWFP (North-West Frontier Province, Pakistan) were analyzed for physical characteristics, inorganic constituents (Na, K, Mg, Fe), and quantification of trace metals such as Pb, Cd, Cr, Zn, Co, Mn, Ni, Ag and Al. The analytical results of the samples were compared with those of a pure heroin sample taken as standard (marked as P). The sodium content was much higher than other inorganic adulterants in almost all the samples, which might be due to the adulteration by common salt (NaCl) and other sodium bearing materials. The calcium and magnesium contents were noted to be higher in the samples from the D. I. Khan (D-1, D-2, D-3), which is an indication of the addition of marble, dolomite and calcite as the heroin adulterants. All the samples contained trace metals in varying concentrations. Samples collected from Peshawar city were found to be highly contaminated and, therefore, contained the least quantity of heroin being 84.97% and 54.54% for samples P-2 and P-3, respectively.